Domske knjižnice: knjižnice v dijaških domovih - Pavletič, Peter (Knjižnica, 2004)
Dormitory libries are not justly treated in Slovenia. They have a double purpose: to develop student literacy, especially reading, critical and creative competence and, moreover, to provide students with opportunities for learning and active spending of free-time. This is made possible by means of agood collection of expertly arranged library material, which is regulary updated and presented to its users, both students and tutors alike. A questionnaire has helped us to find out that libraries in secondary school dormitories carry out their work rather successfully, especially from the viewpoint of poor facilities. The major problems are, nevertheless, the appropriate qualifications of those who fill the posts of librarian and low financial resources. Therefore, such activities should be thoroughly analysed and reconsidered in terms of possible effective solutions, if we want to at least maintain them, let alone develop them.
Keywords: šolske knjižnice; domske knjižnice; dijaški domovi; Slovenia; Slovenija